2016
DOI: 10.4172/2572-5629.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitiligo with Other Autoimmune Disorders

Abstract: Objective: To assess the association of Vitiligo with other autoimmune disorders and to see the familial association.Design: Prospective case control study. Material and methods:Hundred cases of vitiligo of all ages and both genders were included in the study. Diagnosis of Vitiligo was done by clinical examination and was confirmed by Wood's lamp examination. Skin biopsy was carried out for standard pathologic examination to help confirm the diagnosis in two cases. The presence of vitiligo in parents and sibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…This might explain the increased organ-specific autoimmunity observed in ganglion cell destruction as the mechanism of achalasia, leading to their destruction by T cells. Saleem & Azim (2016) [ 17 ] reported that the frequency of associated autoimmune disorders significantly higher in patients with vitiligo than in the control group study. There are some reports of patients with achalasia responding to immunosuppressive drugs, lending further to the suggestion that this disease has an autoimmune component [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might explain the increased organ-specific autoimmunity observed in ganglion cell destruction as the mechanism of achalasia, leading to their destruction by T cells. Saleem & Azim (2016) [ 17 ] reported that the frequency of associated autoimmune disorders significantly higher in patients with vitiligo than in the control group study. There are some reports of patients with achalasia responding to immunosuppressive drugs, lending further to the suggestion that this disease has an autoimmune component [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo is a cutaneous multifactorial disease, affects both sexes equally, higher incidence of females in this study may be result from the greater psychosocial perceived impact of the disease on their life. The presence of positive family history in first degree relative for some patients may indicate a hereditary factor for this disorder (8) .The detection of T-cells infiltration in the perilesional skin of vitiligo macules in previous histopathological studies implicates the cellular immune response in the destruction of melanocytes (9) .Th17 cells play a very important role in the pathogenesis of numerous autoimmune disorders by the production of proinflammatory cytokines includes:IL-17,IL-22 and IL-23, recruit neutrophils, and promote inflammation at the site of infection (10) .In contrast Treg cells inhibit the immune response by the production of anti-inflammatory cytokines include IL-10 and TGF-β which suppress the activity of a variety of immune cells (11) . Several previous studies evaluate the levels of IL-17A and TGF-β1 in the serum of vitiligo patients in alternative countries and reached for the following results: Khan et al (12) reported that the serum level of IL-17A in 45 Indian patients was increased significantly while the serum level of TGF-β1 was decreased significantly as compared with healthy control which came in agreement with the results of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The male: female ratio is 1:1.16. On reviewing various studies conducted on vitiligo by various authors, reported this ratio to be 1:1, 57:76 and 1.19:1 [12][13][14] . Our study is in accordance with other studies.…”
Section: Sexual Preponderancementioning
confidence: 99%
“…After fasting plasma glucose examination, found 16% patients of vitiligo with diabetes mellitus. Previous studies 12,17,18,20 had findings of association of vitiligo and diabetes mellitus. A study 26 showed a significant difference in impaired fasting blood glucose in vitiligo patients.…”
Section: Diabetes Mellitusmentioning
confidence: 99%